The Relationship Between Professional Competence Acquired Through the Teacher Professional Education (PPG) Program and Teaching Readiness of Teachers at SMP Negeri 6 Pangkajene Sidrap - Buhari; Sam Hermansyah; Ibrahim Manda; Rustam Efendi; Nuraini K; Muhammad Hanafi; Muliani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study aims to analyze the relationship between professional competence obtained through Teacher Professional Education (PPG) and the teaching readiness of teachers at SMP Negeri 6 Pangkajene Sidrap. The research employs a quantitative approach with a correlational method to explore how the professional skills acquired from PPG influence teachers' preparedness in delivering lessons effectively. Data were collected through questionnaires, interviews, and documentation, involving teachers who have completed the PPG program as participants. The findings reveal a significant correlation between professional competence and teaching readiness, indicating that the training provided in PPG equips teachers with essential skills and knowledge to enhance their classroom performance. The results of this research provide insights into the importance of professional development programs in improving the quality of education and contribute to strategies for optimizing teacher training initiatives.